The influence of digital radio on the brand equity of commercial radio stations in South Africa - Sibiya, Phushaza (The IIE, 2024)
Commercial radio stations in South Africa continued to see a shift due to digital transformation. This study aimed at understanding the influence of digital radio on the brand equity of commercial radio stations in South Africa. The study considered the perceptions of South African listeners and the adaptation of digital radio. The literature provided a conceptualisation of brand awareness, brand association and brand knowledge. The uses and gratifications theory (UGT) was used to understand better how radio listeners engaged with digital radio to fulfil specific needs. This study was conducted qualitatively, employing semi-structured interviews and thematic analysis for qualitative data analysis. A total number of 12 participants currently residing in South Africa were sampled to share their understanding and experiences of digital radio. Key themes were identified in the process of analysing data, namely the listeners' knowledge of radio, listener perception changes towards radio stations, listener engagement and digital radio platforms, affordability of data and digital adoption alignment of radio features and listener preferences, digital radio stations and new music discovery as well as brand equity and leveraging digital radio. Findings from this research indicated that digital radio plays an essential role in shaping the media landscape and the listeners’ experiences of digital radio. The study also presented recommendations in managerial implications for radio stations to further enhance their brand equity on radio. Key to the findings was the development of content, which spoke to the different lifestyles of listeners.
Keywords: Digital media; Brand equity; Brand perception; Media consumption; Audience engagement; Internet; Radio